Born to be wild - Coulter, Catherine (New York : Jove Books, 2006)
Get yourself ready for Mary Lisa Beverly - a soap-opera phenom who's just won her third Daytime Emmy for her role as Sunday Cavendish on Born to Be Wild. She's fun and lovable and has lots of crazy friends, most of whom hang out at her house in the Colony, the famous gated community in Malibu. Unfortunately, there is one bad thing to poleax her champagne life - someone is trying to kill her. You'll meet Mary Lisa's family in Goddard Bay, Oregon. She's blessed with her father, cursed with her mother, and betwixt and between with her two nutzoid sisters. And how about guys? There aren't any hotties in L.A. of interest to Mary Lisa, but in Goddard Bay - there are District Attorney John Goddard and Chief of Police Jack Wolf. And guess what? Even in the boondocks, bad stuff can happen.
96607
Keywords: Actresses -- United States; Attempted murder; Oregon; California; Romantic suspense fiction; Suspense fiction; Large type books